DFB lasers with apodized surface gratings for wavelength stabilization and high efficiency. (27th June 2017) - Fricke, J; Decker, J; Maaßdorf, A; Wenzel, H; Erbert, G; Knigge, A; Crump, P
Abstract: We present results of GaAs-based distributed-feedback (DFB) broad-area (BA) lasers with integrated surface-etched gratings. Lasers with longitudinally varying (apodized) Bragg gratings are compared to lasers with uniform gratings. DFB-BA lasers with apodized gratings show improved conversion efficiency and output power compared to those with uniform gratings. DFB-BA lasers with narrow contact stripe width W = 30 μ m and resonator length L = 6 mm show a peak conversion efficiency of 60% and maintain efficiency >50% to an output power of >6 W. The spectral FWHM linewidth is below 0.5 nm. Furthermore DFB lasers with implemented apodized gratings are less sensitive to fabrication tolerances.